ANALYSUIS ON CHARACTERISTIC PARAMETERS OF NANO SCALE MOSFETS AND THEIR APPLICATIONS IN LOW POWER VLSI CIRCUITS (International Journal of Food and Nutritional Sciences, 2023)
There is no denying the revolutionary impact that semiconductors have had on society. Although communication and data processing have likely always been essential, the advent of semiconductors has made both incredibly simple and far more efficient than they were, for example, in the era of vacuum tubes. Researchers can therefore pick an appropriate level of abstraction for their needs. Power, speed o performance, silicon area, and cost are the most critical factors in VLSI architectures. Some systems are based on extremely low power operations, while others are performance efficient. There has been a lot of study, but most of it has been at the circuit level. Many different logic architectures and methods for lowering power consumption in circuits have been mentioned in the literature as potential means of accomplishing this goal. As a result, very few methods for achieving that low power design target are provided. In recent years, low power VLSI design has been increasingly interested in sub-threshold logics. The dynamic and leaky power in the super-threshold region can also be decreased by adopting an adiabatic logic style. To account for these factors in complicated circuits, I have provided an analytical model of power dissipation and propagation delay in a subthreshold inverter.